Israelite stories between language and myth - Aldaher, Nada Abdullah (Journal of Arabic Language Sciences and Literature, 2025)
Most of the interpretations included narrations from the Israelites, some of which were raised to the Messenger of God, may God bless him and grant him peace, and perhaps some commentators were enticed by these narrations, and took them as a way to interpret the verses of the Holy Qur'an, and these news are divided into types, including: What Islam approved and testified to its truthfulness is truthful, including: What Islam denied and testified to its lie, it is false, including: What stood from it as a neutral position, and the ways of the commentators differed in their narration, some of them are more than coupled with their chains of transmission such as Al-Tabari, or stripped of the chains of transmission such as al-Baghwi, and some of them mentioned many of them and tracked down Some of what he mentioned by weakening or denial, such as Ibn Kathir, and some of them rejected all and did not mention anything such as Muhammad Rashid Rida, but the understanding of the Holy Qur'an based on the language of its exchange and the like and its significance evacuates such problems and reveals the text,Accordingly, the aim of this research to: Study the compatibility of Israeli novels with the language of the Holy Qur'an in terms of morphological, grammatical and lexicographical, the language is the first and main reference in understanding the texts of the Holy Qur'an, and the fact that the language can not contradict with the reliable novels approved by Islam and agreed with the Israelis, and the research on the analytical approach critical, by reviewing the novel and studying the extent of its conformity with the Holy Qur'an, in terms of language, and the results of the research: The existence of many Israeli narratives is intolerable to language, and therefore these narratives can be rejected and dropped because of the misunderstanding of the Holy Qur'an, distraction from the purpose of the text, and insult to Islam and the prophets.
Keywords: Israeliyyat; semantics (grammatical, morphological, lexical semantics, context); interpretation